Relationships between exchange rate regime, real exchange rate volatility and currency structure of government bonds in emerging markets - Viktar Dudzich (Review of Economic Perspectives, 2020)
Public foreign currency borrowing is a common problem of emerging markets. Scholars named it the original sin of foreign debt. It has a proven negative influence on economic growth and development, undermining financial stability, and increasing the probability of monetary crises. The roots of the original sin often lay in emerging markets' institutional underdevelopment, with low-quality monetary policy, inappropriate exchange rate regime choice, and exchange rate mismanagement being stated among the most important causes. This paper evaluates the influence of the exchange rate policy on the emission of foreign currency sovereign bonds in emerging markets. The relationship is estimated using panel data and GMM approach, with exchange rate regime type (both de jure and de facto) and real exchange rate volatility serving as explanatory variables. The findings reveal that fixed exchange rate regime and high real exchange rate volatility is promoting the foreign currency borrowing. Thus countries that want to reduce the burden of the original sin should lean towards a more flexible exchange rate policy while maintaining their real exchange rate stable.
Keywords: E62; F31; F34; 330; emerging markets; exchange rate regime; original sin; real exchange rate; sovereign bonds